Resectable Gastric Adenocarcinoma Cancer and the Role of Early Feeding on Clinical Outcome - Ida Bagus, Budhi (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Gastric adenocarsinoma is one of the most common gastrointestinal tract cancer, it could be found either in elderly or young patients. Surgical resection is still the main therapeutic option and the gold standard for the resectable cases. Enhanced recovery protocols has been announced to improved the clinical outcome in of gastrointestinal cancer surgery. Especially in upper GI cancer, which still challenging in starting the oral feeding after surgical resection. We will reported the clincal outcome of early feeding on resectable gastric adenocarsinoma patients. Methods: This was a retrospective study, taken from January 2018 - December 2020. All resectable gastric adenocarsinoma patients were included. Tumor locations, type of resection and reconstruction were evaluated. All patients had early oral feeding from the first post operative day, continued with liquid and semi solid food. The short term outcome were recorded including the anastomose leakage and surgical site infection. Results: We reported eight gastric cancer patients during this study, 1 patient was young gastric cancer patiens and the rest were > 50 years old patients. Gastric anthrum was the most common tumor site with partial gatrectomy and Billroth II have been done. 3 patients were corpus site and 1 case of fundus cancer, total gastrectomy and roux en y esófago-jejunostomy reconstruction was done. We found no anastomosis leakage. No SSI and no readmission associated with post operative morbidity. Conclusion: Early feeding on resectable gastric adenocarsinoma patients was feasibel, has good clinical outcomes and could tolerated well, no matter what type of gastric resection we did.